2017
DOI: 10.4038/cmj.v62i1.8428
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of dug well water from an area with high prevalence of chronic kidney disease of unknown etiology (CKDu) and development of kidney and liver lesions in rats

Abstract: Introduction Chronic kidney disease of unknown aetiology (CKDu) is prevalent in the North Central Province (NCP) of Sri Lanka and ingestion of dug well water is considered a potential causative factor. Three CKDu prevalent villages were selected from the NCP based on the number of CKDu patients in the locality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…A previous study by our group revealed a significant association between consumption of dug well water collected from CKDu affected villages and the development of periglomerular and peritubular interstitial nephritis in Wistar rats, compared to rats that ingested water collected from a low disease prevalence area; Colombo, in the wet zone of Sri Lanka [8]. However, the disease prevalence is not uniform in the NCP.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…A previous study by our group revealed a significant association between consumption of dug well water collected from CKDu affected villages and the development of periglomerular and peritubular interstitial nephritis in Wistar rats, compared to rats that ingested water collected from a low disease prevalence area; Colombo, in the wet zone of Sri Lanka [8]. However, the disease prevalence is not uniform in the NCP.…”
Section: Introductionmentioning
confidence: 76%
“…As the majority consume un-boiled dug well water (83%), Arsenic (as as) (0.001 mg/L) ND ND ND ND ND ND Cadmium (as Cd) (0.001 mg/L) ND ND ND ND ND ND NTM: NTMB boiled, BB, DD, HW, CO water samples analysis at the Industrial Technology Institute, Colombo, Sri Lanka Not detectable levels: Total Iron; below 0.1, Arsenic: below 0.001, Cadmium: below 0.001 New Town Medirigiriya (NTM), Boiled water from Medirigiriya (NTMB), Bisobandaragama (BB), Divuldamana (DD) from high disease endemic areas for CKDu of unknown origin and Huruluwewa (HW) and Colombo (CO) that were used as controls from low endemic areas (n = 10) All the values are expressed with Standard Error (SE) and precisions were done in 95% confidence intervals (p < 0.05) the authors hypothesized that including a boiled water sample from an area with the highest disease burden (NTM) will have some impact on the experimental design. As such, dug well from NTM was selected to represent boiled as well as un-boiled water considering the very high disease burden in the locality [8,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table VII shows that Sri Lankan Chronic Kidney disease is uncorrelated with Cd in rice. Hence other explanations have been conidered [66,72]. The Codex Alimentarius [11] uses a single-variable stepfunction model for stipulating a chronic toxicity-onset amount m Cd per kg of body weight per day, week or month, as is appropriate.…”
Section: B Model Based On Harvest Volumementioning
confidence: 99%